Phenomenology of toxic behavior in language use by children in Wanasalam village, Banten - Hadinata, Vicentius Michael; Fadillah, Dani (Journal of Social Studies (JSS), 2024)
This research examines the phenomenology of toxic behavior of children in kp. Wanasalam, Banten, with a focus on the object of children in kp. Wanasalam. This research aims to analyze the factors and also the reasons why a child can behave toxicly in the environment where he lives and also why these factors can be the reason for children to behave toxicly. This research was conducted in Banten Province, Lebak Regency, Wanasalam Village. This research uses a qualitative approach with phenomenological theory according to Husserl (1938) with a case study method. The data in this study were collected through direct observation in kp. Wanasalam. The sample was selected based on a certain age range, aged 7-12 years. Based on the results in this study, it has been found that a child's toxic behavior is caused by toxic parenting, besides that the environment or culture in an area is also one of the causes of why a child can behave toxicly. To overcome children's bad behavior in Banten Wanasalam village, several actions can be taken such as education and character development, social network development, mental health improvement, and rehabilitation programs that involve families and local communities In addition, it is also important to involve local stakeholders such as the head of the rt and rw in prevention and intervention efforts to improve children's behavior social environment of children in wanasalam village.